2010
DOI: 10.1007/s00232-010-9236-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biochemical Pathways for 5-Fluorouracil in Managing Experimental Hepatocellular Carcinoma in Rats

Abstract: Five fluorouracil (5-FU) is extensively used in the treatment of hepatocellular carcinoma (HCC). It is well documented that 5-FU and its metabolites inhibit DNA synthesis through inhibition of thymidylate synthetase. Little is known about additional pathways for 5-FU in managing HCC. The present experiment was mainly designed to study possible biochemical pathways that can be added to 5-FU's mechanisms of action. Four groups of rats constituted a control group (given saline only), a trichloroacetic acid group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…This early upregulatory impact of TCA on proteolytic enzymes may contribute to the mechanism of cancer induction and invasion by this substance, an action that was noticed in some previous publications [39, 40]. Administration of AOLE alone maintained some proteolytic enzyme activities within normal values, except an elevation of papain activity to a significant level.…”
Section: Discussionsupporting
confidence: 63%
“…This early upregulatory impact of TCA on proteolytic enzymes may contribute to the mechanism of cancer induction and invasion by this substance, an action that was noticed in some previous publications [39, 40]. Administration of AOLE alone maintained some proteolytic enzyme activities within normal values, except an elevation of papain activity to a significant level.…”
Section: Discussionsupporting
confidence: 63%
“…41 Similar to our standpoint, AbdeHamid NM et al reported that some anticancer drugs that did not show typical antimetastatic effects, such as 5-Fu, could not inhibit sia levels in tumor cells. 44 These work show the inhibitions of sias in tumors can be a good model to study antimetastatic drugs than antiproliferative drugs and be significance for studying their underlying mechanisms. This is a relatively new therapeutic target for us to study.…”
Section: Experimental Therapeutic Studymentioning
confidence: 99%
“…It involved from bioassays to anti-proliferative evaluation to anti-metastatic responses in murine tumor models (Lewis lung carcinoma and melanoma B16). The therapeutic studies of sias-related Antimetastatic drugs began at approximately 30 years ago [12,25,[36][37][38][39][40][41][42][43][44][45][46]. Since this type of anticancer drugs (especially targeting sias in tumors) has been seldom entering into clinical investigations, most experimental therapeutic studies have been collected here.…”
Section: Experimental Therapeutic Studymentioning
confidence: 99%
“…However, some licensed anticancer drugs such as 5-Fu that do not show typical Antimetastatic effects are also unable to inhibit sialic acid levels in tumor cells [44].…”
Section: Experimental Therapeutic Studymentioning
confidence: 99%